Congenital malformations in multiple births - Menasinkai, Sharada B.; R., Dakshayani K.; Chiniwar, M. A. (International Journal of Research in Medical Sciences, 2017)
Objective: The present study was done to know and compare the incidence of congenital malformations in singleton and multiple births in our hospital & compare with other studies. Methods: A retrospective study done by collecting the data from parturition register from Jan 2008 to Dec 2011 (4yrs) from Cheluvamba Hospital attached to Mysore Medical College and Research Institute. Total number of the live births, still births, and abortions> 20 wks were collected. Details of multiple births such as maternal age, gestational age, sex & birth weight of the babies, U/S reports and congenital anomalies (CA) were noted. Results: The total number of singleton births were 48700 and number of babies who had congenital malformations were 235 (48.25/10,000 births).Total number of multiple births were 579 including 10 triplets and number of babies who had CA were 11 (189.98/10,000 births, P<0.0001). In the present study sex of the babies were noted in all multiple births and zygosity could not be recorded. Among 579 multiple births 404 were of the Same Sex (SS) and 165 were of Opposite Sex (OS) in twins and 6 were of the same sex and 4 were of opposite sex in triplets. According to Weinberg formula 50% of same sex (SS) twins are monozygotic and 50% are dizygotic twins. Among the 11 babies with CA, 4 monozygotic twins had anomalies related to twinning such as Acardia with TRAP sequence (3 twins), and Thoracophagus (1 twin).5 babies had CNS anomalies, 1 with cystic hygroma, 1 baby with multiple system affected. Conclusion: The incidence of birth defects is more in multiple births and especially in monozygotic twins. In the present days increase in twinning rate due to advanced maternal age, hereditary factors and use of ovulation inducing drugs, which results in premature and low birth wt babies associated with poor lung maturity.